Effect of commercially available bioaugmentors on the removal of ammonia and sulphide from brackishwater - Joseph, K O; Muralidhar, M; Gupta, B P; Krishnani, K K (Indian Journal of Fisheries, 2011)
The levels of amonnia and sulphide, when exceeded the critical limit became toxic to aquatic life in brackishwater systems. An experiment was conducted in laboratory to test the efficiency of commercially available materials viz. health stone, BN-10 and zeolite powder in removing ammonia and sulphide from brackishwater. Health stone + BN-10 combination was significantly (P<0.05) superior over other treatments in decreasing ammonia (71.6%), whereas, other treatments including bioaugmentors were not effective when applied alone. Zeolite was not effective in brackishwater system for ammonia removal. Sulphide removal was 100% by 3rd day with zeolite alone and health stone + BN- 10 combination